Rancangan Alat Bantu Pembelajaran Daur Hidup Hewan Untuk Siswa SLB Bagian B Tunarungu Berbasis Multimedia - Berry Juanda Prawira; Diana Effendi (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2020)
Children with special needs are individuals who are not much different from children in general, but in carrying out educational activities still have obstacles. One of the children with special needs is a deaf child who receives a variety of subject matter, one of which is animal life cycle material in science subjects. In the process of delivering the material is still done conventionally, the teacher conveys through cues so that it becomes an obstacles to deliver material that requires visuals about the processes that occur in the material. The purpose of this study is to create a multimedia application of learning the life cycle of animals to help deaf students in SLBN Cicendo in visualizing the material. The author uses qualitative descriptive research methods, data collection methods using interviews, system development models using prototypes, and tools to design applications using Unified Modeling Language (UML). Based on the design of the application made, the application is built using Adobe Flash CS6 Professional software, so it is expected to help the delivery of material to deaf students more easily and attractively.